Enhancing Digital Technology Education for School Children - Fransina Latumahina; Muhammad Edy Sudarmono; Amri Aurulianto; M. Ishan Umahuk; Kahar Hitimala (Universitas Muhammadiyah Sidoarjo, 2023)
Enhancing digital technology education for school children has become imperative in the rapidly evolving digital era. This abstract provides an overview of the importance of digital technology education, outlining its goals, benefits, and implementation approaches. It emphasizes the need to equip children with the necessary skills and knowledge to responsibly and effectively navigate the digital realm. The role of educators in designing directed and innovative learning experiences using digital technology is discussed, along with the significance of collaborative learning, creativity, and problem-solving in a technological context. Moreover, this abstract underscores the importance of integrating digital ethics, online security awareness, and privacy protection within digital technology education. By adopting this comprehensive approach, children can develop robust digital literacy skills, enabling them to adapt to ongoing technological changes and tackle challenges and opportunities in our digitally-driven world. This research further highlights the implications and suggests future investigations to gain a deeper understanding of the impact and long-term effects of digital technology education on school children, providing valuable guidelines and recommendations for educators, schools, and stakeholders to enhance its effectiveness and efficiency.Highlight: Digital technology education enhances cognitive skills, critical thinking, and problem-solving abilities among school children. It fosters creativity through the use of digital tools, allowing children to engage in digital art, design, and creative projects. It promotes collaboration and communication, enabling teamwork and idea-sharing through collaborative tools. Keyword: Digital Technology Education, School Children, Cognitive Skills, Creativity, Digital Ethics